NEW APPROACHES IN THE TREATMENT OF DIABETIC OSTEOARTHROPATHY - Bobobekov, A.R.; Makrounashi, C. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The frequency of lower limb amputations in patients with diabetic foot syndrome complicated by osteoarthropathy is 15-20 times higher than in the general population and accounts for 50-70% of the total number of all non-traumatic amputations. At the same time, in patients with type 2 diabetes mellitus, at the time of diagnosis, from 30 to 50% of patients have signs of damage to the lower extremities of one degree or another. Material. Under our supervision at the clinical base of the Tashkent Medical Academy there were 96 patients with osteoanthropic form of diabetic foot syndrome. Results. Standard treatment without the use of immunomodulators reduces the severity of immune disorders, but the normalization of the studied indicators does not occur (with the exception of the level of immunoglobulin A). The inclusion of glutoxime in the treatment regimen leads to a preferential correction of the level of interleukin-1ß, interleukin-10 and oxygen-dependent bactericidal activity of neutrophils. Conclusion. When using polyoxidonium, the highest degree of correction of phagocytosis and cellular adaptive immunity was noted: neutrophil stimulation index, oxygen-dependent bactericidal activity of neutrophils and CD8+ lymphocyte count.